Clinical Cases in Geriatric Dermatology - Norman, Robert A.; Endo, Justin (Clinical Cases in Dermatology,, 2013)
The demographic imperative has reached the shores of dermatology.  By 2020 those aged 65 years and older will comprise a quarter of the US population, and this percentage will be even more significant in less developed countries. As a specialty, dermatology needs to respond to this unprecedented demographic shift.  Over the last few decades dermatology has enjoyed a sustained improvement in understanding of the basic science of skin biology and an increase in proven effectiveness of clinical interventions.  As dermatologists, leadership must be in place to provide specialized care for older adults; dermatology should be at the forefront of prevention and treatment of skin diseases and be able to recognize the dermatologic signs of chronic systemic disease so often noted in our elderly. Clinical Cases in Geriatric Dermatology represents a practical tool in understanding the skin of older people and includes chapters on the common presentations of dermatologic disease in the elderly population. It presents practical information to assist in making the correct clinical decision. The concise case-based organization of this book will help those in dermatology training programs, but will also be a welcome revision tool for qualified and recertifying dermatologists.